Lasheen technique for lengthening of spermatic cord in management cryptorchidism (Lasheen spiral spring) - Ahmed E Lasheen (Journal of Surgery and Surgical Research - Peertechz Publications, 2020)
<p style="box-sizing: border-box; margin: 0px 0px 10px; color: rgb(51, 51, 51); font-family: Merriweather, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: rgb(255, 255, 255); text-decoration-style: initial; text-decoration-color: initial;">Background: Undescended testis is the most common anomaly of male genitalia. In these cases the testis lies at any position other than the normal scrotal position. The goal of surgery is to move the testis to scrotum, but short spermatic cord represent the big problem. Our study offers new technique for lengthening spermatic cord depends on tissue expansion theory. <p style="box-sizing: border-box; margin: 0px 0px 10px; color: rgb(51, 51, 51); font-family: Merriweather, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: rgb(255, 255, 255); text-decoration-style: initial; text-decoration-color: initial;">Methods: Twenty one undescended high inguinal testis patients were included in our study. After complete dissection of testis and spermatic cord of surrounding tissue through inguinal incision. Fine spring made of delicate steel spiral wire was put around cord to produce fine continuous pushing force on testis and spermatic cord toward the scrotum. The inguinal wound was closed with spiral spring in right position and proximal end of spring fixed at the skin by one stitch. After the testis reach normal scrotal position, the spring removed by applied light traction with clockwise rotation on proximal spring end. The mean follow up period was 12 months (ranging from 6 to 18 months). <p style="box-sizing: border-box; margin: 0px 0px 10px; color: rgb(51, 51, 51); font-family: Merriweather, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: rgb(255, 255, 255); text-decoration-style: initial; text-decoration-color: initial;">Results: The mean patients age was 2.5 years (ranging from 1 to 4 years). Congenital inguinal hernia sacs were presented in 15 cases, which excised during surgery. The time needed for putting the testis at the bottom of scrotum ranged from 3 to 4 weeks. The testis was normal in position, vasculature, and size during follow up period by manual examination and Doppler study. <p style="box-sizing: border-box; margin: 0px 0px 10px; color: rgb(51, 51, 51); font-family: Merriweather, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: rgb(255, 255, 255); text-decoration-style: initial; text-decoration-color: initial;">Conclusion: Lasheen technique for lengthening of spermatic cord is safe, easy, and effective in management of undescended testis.